Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

What is the easiest way to evaluate this limit? $\displaystyle{\lim_{n \to\infty} \left(n-1 \over 2n+2\right)^n}$ $$ \text{Is this possible ?$\,$:}\quad \lim_{n \to\infty}\left(n/n - 1/n \over 2n/n + 2/n\right)^n = \lim_{n \to\infty}\left(1 - 1/n \over 2 + 2/n\right)^{n} = \lim_{n \to\infty} \left(1 \over 2\right)^{n} = 0 $$

share|improve this question
    
What if it was $\left(\frac{n-1}{n+2}\right)^n$? –  Siméon Nov 25 '13 at 15:18
    
This addresses a previous version of the question. <hr> Sorry but $$\lim_{x \to\infty} \left(\frac{n-1} {2n+2}\right)^n=\left(\frac{n-1} {2n+2}\right)^n.$$ –  Did Nov 25 '13 at 15:19
1  
The last line is wrong: you have $\lim \ (1-{1 \over n})^n=\exp(-1)$. Also, in all your limits, the variable is $n$, not $x$. Apart from that, your result is trivially true, since ${{n-1} \over {2n+2}}<1/2$. –  Jean-Claude Arbaut Nov 25 '13 at 15:19
1  
@LukaToni, isn't the limit for $n,$ instead of $x?$ –  lab bhattacharjee Nov 25 '13 at 15:19
1  
"Solve" is the wrong word. "Evaluate" would be appropriate. One solves problems; one solves equations; one evaluates expressions. –  Michael Hardy Nov 25 '13 at 16:14

7 Answers 7

up vote 16 down vote accepted

For simple limits like this, the easiest way is often to sandwich the sequence between simpler sequences for which the limit is known.

Notice that $n-1 \leq n$ and $2n+2 \geq 2n$ entail $$ \frac{n-1}{2n+2} \leq \frac{1}{2} $$ so that for $n \geq 1$ one has $$0 \leq \left(\frac{n-1}{2n+2}\right)^n \leq \left(\frac{1}{2}\right)^n \xrightarrow[n\to\infty]{} 0.$$ Conclude with the squeeze theorem.

Remark. This method gives more than just the limit: you get a good estimate of how quickly the sequence converges. For example, it is now easy to give a $n$ such that $\left(\frac{n-1}{2n+2}\right)^n \leq 10^{-100}$.

share|improve this answer

The limit can be written as $$\frac{\left(\lim_{n\to\infty}\left(1-\frac1n\right)^{-n}\right)^{-1}}{\lim_{n\to\infty} 2^n\cdot \lim_{n\to\infty}\left(1+\frac1n\right)^n}$$

Now use $$\lim_{m\to\infty}\left(1+\frac1m\right)^m=e$$

share|improve this answer
    
Is this incorrect, another joke, or a legitimate alternative solution? –  kaine Nov 25 '13 at 15:31
4  
@kaine, why? It becomes $$\frac{e^{-1}}{\infty\cdot e}=0$$ –  lab bhattacharjee Nov 25 '13 at 15:32
    
Ok, that is correct.. I didn't follow the solution at first but now it makes sense. –  kaine Nov 25 '13 at 15:35

$0\le\left(\dfrac{n-1}{2n+2}\right)^n=\dfrac{1}{2^n}\times\dfrac{\left(1-\dfrac{1}{n}\right)^n}{\left(1+\dfrac{1}{n}\right)^n}\le\dfrac{1}{2^n}\times\dfrac{1}{\left(1+\dfrac{1}{n}\right)^n}\to0$ since $\left(1+\dfrac{1}{n}\right)^n\to e$

So by squeezing $\displaystyle{\lim_{n \to\infty} \left(n-1 \over 2n+2\right)^n}=0.$

share|improve this answer

$\newcommand{\+}{^{\dagger}}% \newcommand{\angles}[1]{\left\langle #1 \right\rangle}% \newcommand{\braces}[1]{\left\lbrace #1 \right\rbrace}% \newcommand{\bracks}[1]{\left\lbrack #1 \right\rbrack}% \newcommand{\dd}{{\rm d}}% \newcommand{\isdiv}{\,\left.\right\vert\,}% \newcommand{\ds}[1]{\displaystyle{#1}}% \newcommand{\equalby}[1]{{#1 \atop {= \atop \vphantom{\huge A}}}}% \newcommand{\expo}[1]{\,{\rm e}^{#1}\,}% \newcommand{\fermi}{\,{\rm f}}% \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,}% \newcommand{\ic}{{\rm i}}% \newcommand{\imp}{\Longrightarrow}% \newcommand{\ket}[1]{\left\vert #1\right\rangle}% \newcommand{\pars}[1]{\left( #1 \right)}% \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}}% \newcommand{\root}[2][]{\,\sqrt[#1]{\,#2\,}\,}% \newcommand{\sech}{\,{\rm sech}}% \newcommand{\sgn}{\,{\rm sgn}}% \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}}% \newcommand{\verts}[1]{\left\vert #1 \right\vert}% \newcommand{\yy}{\Longleftrightarrow}$ $$ \color{#0000ff}{\large\lim_{n \to\infty} \left(n - 1 \over 2n + 2\right)^{n}} = \lim_{n \to\infty}\bracks{{1 \over 2^{n}}\, {\pars{1 - 1/n}^{n} \over \pars{1 + 1/n}^{n}}} = \lim_{n \to\infty}\pars{{1 \over 2^{n}}\,{\expo{-1} \over e}} = \color{#0000ff}{\large 0} $$

share|improve this answer

$$\frac{n-1}{2n+2} = \frac{1}{2}\frac{n+1}{n+1}-\frac{1}{2}\frac{2}{n+1}$$ $$\lim _{n \rightarrow \infty}(\frac{1}{2}-\frac{1}{n+1})^n$$ which is less than your $\frac 1 2$ so it does go to $0$

share|improve this answer

Another approach:

$$\left(\frac{n-1}{2n+2}\right)^n=\frac1{2^n}\left(1-\frac2{n+1}\right)^n=$$

$$=\frac1{2^n}\left(1-\frac2{n+1}\right)^{n+1}\left(1-\frac2{n+1}\right)^{-1}\xrightarrow[n\to\infty]{}0$$

since the second factor's limit above is $\;e^{-2}\;$ , and the third's is $\;1\;$

share|improve this answer

You can calculate this limit easily by using the root test: First, we have to make sure that the sequence is bigger or equal to 0 for all n, i think it is quite easy to see it and then: $$a_n = \left(\frac{n-1}{2n+2}\right)^n$$ $$(a^n)^{1/n}=\frac{n-1}{2n+2} \rightarrow \frac{1}{2}$$ Therefore, by the root test: $$a_n \rightarrow 0$$ You can find about the root test here: http://en.wikipedia.org/wiki/Root_test, though in this link, it looks more complicated.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.